A institucionalização das representações sociais da agroecologia na agricultura familiar - Guerra, Gilberto Clarício Martinez (2010)
In Brazil, due to Green Revolution, it was initiated in the end of years 1960, the use of seeds improved genetically, barren in its majority, agrotoxics and agrochemicals, that caused ambient damages and the social exclusion of the small familiar agriculturist, because the debts and damages to its health. With the understanding of the unsustainability of the conventional system, the agroecology - that it is a science that establishes the bases for the construction of styles and strategies for the sustainable agricultural development - was developing itself, existing in it three levels that they need to be related between itself: ecological, economic and social (first level); cultural and politics (second level) and ethics (third level). In this context, in Paraná is the IAPAR (Agronomic Institute of Paraná) that carries through many of the agroecologist research in the state, by means of the PAG (Program of Research in Agroecology) and are the agricultural extensionists of the EMATER (Paraná Institute of the Technique Assistance and Agricultural Extension) that they carry through the actions of orientation and motivation to convert the conventional agriculturists into agroecologists. The agriculturist, mainly the familiar one, is that one that receives the orientations from the extensionists of the EMATER in regards to the agroecology. Ahead of this, and knowing the present time of the subject, it was understood as important to know the understanding that these actors have of the agroecology and the process for which it passes in legitimation search. So, the objective of the present work is to understand the institutionalization of the social representation of the agroecology for researchers of the IAPAR, extensionists of the EMATER and agricultural producers of familiar agriculture that work with it, on the basis of the beliefs, values and standards of actions of these actors, in the city of Umuarama-PR, the period of 2004 the 2009. The dissertation has as base the alliance between the Theory of the Social Representations and the Neoinstitucional Theory. By means of a qualitative and descriptive methodological means, using mainly half-structuralized scripts for interviews, the analysis of speech unmasked the diverse social representations of the three involved actors with the agroecology. These representations possess similarities, as the concern with the health of the agriculturist, the ambient and economic support; and also distinctions, in the priorities with that each one perceives these dimensions, beyond pointing the difficulties and expectations of the actors. With the support of the Neoinstitucional Theory, the process of institutionalization of the agroecology for the three involved actors with agroecologists works was illustrated. One noticed that the beliefs and values necessary to accept the agroecology were formed in the basic education, for the institutions school and family. Due to radical change in estimated orienting and the standards of actions, the process of objetivation and anchorage of the agriculturists were most complex between the three searched actors. For extensionists and agriculturists, the legitimation still is difficult of being reached, because the preconceptions and indifferences that the agroecology still suffers in its areas, whereas for the researchers it more is institutionalized. It was possible to conclude that the object of the representation and the institutionalization still possess obstacles, for going against the chain of effective thought.